Penerapan Search Engine Optimization Untuk Meningkatkan Peringkat Website Pada Search Engine Results Page Google (Studi Kasus: www.superbengkel.co.id) - Fabriyan Fandi Dwi Imaniawan; Ragil Wijianto; Joko Dwi Mulyanto (Universitas Bina Sarana Informatika, 2020)
AbstractThe development of internet-based technology has become a media for spreading information which is faster and more efficient than other media, such as print and electronic media. It is what drives a number of business owners to start exploring the digital world by opening websites and social media to promote their businesses. Multi Jaya Press is a company in Banyumas Regency which is engaged in the sale of motorcycle press tool and workshop installation services. In the marketing process,, Multi Jaya Press uses media in the form of a website which is located at www.superbengkel.co.id. The use of the website is still not optimal for searching several targeted keywords, thus the website is difficult to be found by the google search engine organically. Generally, a website owner will make a quick decision to solve this problem using paid Google ads. Although it can appear on the top page of google search, the use of paid Google ads will cost a lot of money. It is clearly seen when a website uses google ads, it will be labeled as an